Determine the values of K such that the quadratic equation x^2 + 2Kx - 3K =0 has equal roots

Thankyou

3 answers

2x^2 - kx - 3=0
just plug in 3 for x and solve for k
2*3^2 -3k - 3=0
2*9-3k-3=0
15=3k
5=k
why plug in 3 for x?
Why change the polynomial?

x^2 + 2kx - 3k = 0
the discriminant is (2k)^2 - 4(1)(-3k) = 4k^2 + 12k

For two equal roots, the discriminant must be zero.

4k^2+12k = 4k(k+3) = 0
k = 0 or -3

k=0: clearly x^2=0 has two equal roots
k = -3: x^2-6x+9 = (x-3)^2 has two equal roots.
I agree with you messed up my math.